(untitled) (Journal of Sciences & Technology, 2020)
Batch adsorption process of metal pollutants in aqueous phase can be influenced by several parameters such as initial pH of the solution, dose of the adsorbent, concentration of the adsorbate, contact time, temperature, agitation rate and adsorbent characteristics. In this study Taguchi’s statistical approach was used to optimize the parameters of Cr(VI) biosorption by eucalyptus leaf powder. The orthogonal array L9 with three levels was applied to determine the optimal conditions for adsorption. The obtained results show that Cr(VI) removal is maximum (96.51%) with the low level of initial pH solution (1.0) and initial metal concentration (50 mg/L) and, with the high level of the adsorbent dose (3.0 g/L) and contact time (70 min). The analysis of variance of the experimental results, carried out for a level of significance of 5%, revealed that the initial pH solution is the most important parameter influencing the adsorption efficiency of chromium (VI) with a percentage contribution of 47.60%.